STRUKTUR JARINGAN DALAM ADOPSI INOVASI: STUDI KONSEPTUAL (IAIN Tulungagung, 2015)
Deployment of innovations to the social system is believed to be a trigger of changes in society. How the dissemination of innovation in society can be explained is the question you want to discuss in this article. Specifcally, this paper aims to describe how the theory of social networks (social network analysis) can be used to explain the adoption of innovation. It emphasized in relation to the network structure characteristic of innovation adoption decisions as a result of the effects of imitation behavior and the effect of actor innovation. Keywords: adoption, diffusion, innovation, network structure, imitation behavior